Somalia : Technical Assistance Report-Bank Supervision and Regulation. (IMF Staff Country Reports; Country Report, 2021)
The purpose of the missions of Phase I was to develop a functional central bank, including establishing a modern banking supervisory regime. Especially, MCM provided TA missions under the Phase I that have focused on operationalizing banking license capacity, development of on and offsite supervisory capability, and other relevant areas.